A Study of the Social Media Important for E-Commerce: Exploring the Impact and Potential of Social Media for E-commerce Success (Journal of Advances and Scholarly Researches in Allied Education, 2020)
With the rapid advancement of technology, social media has emerged as a powerful platformthat revolutionizes the way businesses engage with customers and conduct e-commerce. This reviewarticle aims to provide an in-depth analysis of the importance of social media in the realm of ecommerce.We explore various aspects of social media, including its impact on consumer behavior,brand visibility, customer engagement, sales generation, and market research. By examining currentresearch and industry practices, this review article provides valuable insights into harnessing the fullpotential of social media for e-commerce success.